Titik Beranjak Nurcholish Madjid: Dari Masa Kanak-kanak Sampai Tradisi Pesantren - Ahmad Gaus AF (Budapest International Research and Critics University, 2018)
Nurcholish Madjid was a prominent Indonesian Muslim intellectual. Early in his academic career, Nurcholish was a leader in various student organizations. He soon became well known as a proponent for modernization within Islam. Throughout his career he continued to argue that for Islam to be victorious in the global struggle of ideas, it needs to embrace the concepts of tolerance, democracy and pluralism.